African American Digital Practices: Mobile E-Health and Residential Segregation. Issue 3 (3rd July 2018) - Graham, Roderick S.; Smith, Shawn K.
ABSTRACT: We ask two questions about the relationship between race, using mobile phones for e-health, and living in segregated neighborhoods: Are racial differences associated with using mobile phones for e-health, especially as they relate to African Americans? Is living in segregated neighborhoods associated with changes in mobile phone usage? We merge the National Trends Survey (HINTS) conducted by the National Cancer Institute, for information on e-health, and the US 2010 project, for the necessary measures of residential segregation. Multilevel models (Level 1  N  = 2, 023, Level 2  N  = 183) produced two major conclusions. First, African Americans exhibit unique "digital practices" vis-à-vis e-health, such that they use e-health to share personal diagnostic information less than whites but use e-health for more practical, logistical uses than do whites. Second, residential segregation is associated with digital practices; however, considering racial differences in where people live does not reduce racial differences in e-health patterns.